Affibody-Modified Gd@C-Dots with Efficient Renal Clearance for Enhanced MRI of EGFR Expression in Non-Small-Cell Lung Cancer [Corrigendum] - Wu Y; Li H; Yan Y; Wang K; Cheng Y; Li Y; Zhu X; Xie J; Sun X (International Journal of Nanomedicine, 2025)
Wu Y, Li H, Yan Y, et al. Int J Nanomedicine. 2020;15:4691—4703. The authors have advised due to an error that occurred inadvertently at the time of figure assembly, the MRI images at the 2 hour time point in Figure 6A and the 10 minute time point in Figure 6B on page 4700 are incorrect. The correct Figure 6 is as follows.